MECHANISMS TO ACTIVATE STUDENT INDEPENDENT LEARNING - Hayitova Shakhnoza Daniyarovna (Journals Park Publishing, 2022)
This article discusses the work being done by higher education institutions today to develop students' independent learning activities, and the challenges they face in this process
Keywords: education; independent learning; competence